Eriophyoid mite fauna from Henan Province, central China (Acari: Eriophyoidea) with descriptions of five new species - Xue, Xiao-Feng; Hong, Xiao-Yue (Zootaxa, 2006)
Thirty-seven eriophyoid mites from central China’s Henan Province, including five new species, are described and listed: Boczekella fabris sp. nov. on Abies fabri (Mast.) Craib (Pinaceae); Trisetacus ehmanni Keifer on Larix kaempferi (Lamb.) Carr. (Pinaceae); Setoptus koraiensis Kuang & Hong on Pinus thunbergii Parl. (Pinaceae); Eriophyes armandis sp. nov. on Pinus armandi Franch. (Pinaceae); Acaphyllisa populi sp. nov. on Populus sp. (Salicaceae); Epitrimerus amygdali Xue & Hong on Amygdalus triloba (Lindl.) Ricker (Rosaceae); Epitrimerus sabinae Xue & Hong on Sabina chinensis (L.) Antoine and Sabina chinensis cv. Kaizuca (Cupressaceae); Paraepitrimerus erigeronsis Xue & Hong on Erigeron annuus (L.) Pers. (Compositae); Paraepitrimerus paeoniae Xue & Hong on Paeonia lactiflora Pall. (Ranunculacear); Phyllocoptes fabris Xue & Hong on Abies fabri (Mast.) Craib. (Pinaceae); Phyllocoptes taishanensis Xue & Hong on Cedrus deodara (Roxb.) Loud (Pinaceae); Abacarus wuyiensis Kuang & Zhuo on Bambusa sp. (Gramineae); Aculodes bambusae Kuang on Bambusae sp. (Gramineae); Aculops taihangensis Hong & Xue on Ailanthus altissima (Mill.) Swingle (Simaroubaceae); Aculops strobilaceae sp. nov. on Platycarya strobilacea Sieb. & Zucc. (Juglandaceae); Aculus altissimae Xue & Hong on Ailanthus altissima (Mill.) Swingle (Simaroubaceae); Aculus amygdali Xue & Hong on Amygdalus persica L. (Rosaceae); Aculus bambusae Kuang on Bambusa sp. (Gramineae); Aculus coggygriae Xue & Hong on Cotinus coggygria Scop. (Anacardiaceae); Aculus huixiansis Xue & Hong on Salix sp. (Salicaceae); Aculus populi Xue & Hong on Populus sp. (Salicaceae); Aculus salicis Kuang & Luo on Salix sp. (Salicaceae); Anthocoptes japonicae sp. nov. on Sophora japonica L. (Leguminosea); Heterotergum artemisiae Hong & Kuang on Artemisia sp. (Compositae); Neotetra bambusae Kuang on Bambusa sp. (Gramineae); Tegolophus hunanensis Lin, Jin & Kuang on Vitex negundo var. cannabifolia (Sieb. & Zucc.) Hand.-Mazz. (Verbenaceae); Tegolophus zizyphagus (Keifer) on Ziziphus montata Smith (Rhamnaceae); Tetra formosae Xue & Hong on Lespedeza formosa (Vog.) Koehne (Leguminosae); Tetra japonicae Xue & Hong on Sophora japonica L. (Leguminosae); Tetra lobatae Xue & Hong on Pueraria lobata (Willd.) Ohwi (Leguminosae); Tetra suspensae Xue & Hong on Forsythia suspensa (Thunb.) Vahl (Compositae); Diptacus songxianensis Xue & Hong on Ulmus sp. (Ulmaceae); Trimeroptes aleyrodiformes (Keifer) on Dendrobenthamia japonica var.chinensis (Osborn) Fang (Cornacear); Trimeroptesluanchuanensis Xue & Hong on Rubus sp. (Rosaceae); Brevulacus reticulatus Manson on Quercus glauca Thunb. (Fabaceae); Rhyncaphytoptus acer Chen, Wei & Qin on Acer sp. (Aceraceae) and Rhyncaphytoptus longipalpis Xue & Hong on Bambusa sp. (Gramineae). All species are vagrant on and under leaves. A key to the eriophyoid mites from Henan Province is provided.